Alcohol and the college athlete - Nelson, T. F.; Wechsler, H. (Medicine & Science in Sports & Exercise, 2001)
Summary This study was designed to examine alcohol use and binge drinking in college athletes. 12,777 college students, of whom 2,172 were classified as athletes, were randomly selected from 130 universities to complete a survey on alcohol use. The study was designed to examine alcohol use, look at the incidence of alcohol related "harms" (ranging from legal trouble to academic problems) and try to identify the reasons for alcohol consumption. Findings Among males, athletes were more likely to engage in binge drinking than their non-athletic peers (57% to 48.8%, p<0.001). Among females, athletes again were more likely to engage in binge drinking than their non-athletic peers (48% to 40.2%, p<0.001). Athletes reported a more extreme drinking style, often stating that drinking to get drunk was an important reason for drinking. Athletes were more likely to experience alcohol related harms than non-athletes (some examples given included drunk driving, being a victim of a crime, unplanned sexual activity, missing class and falling behind in schoolwork). Athletes tend to exhibit more of the social characteristics associated with drinking (examples given included thinking parties were important, have friends that binge drink, and having more friends than the average non-athlete). Binge drinking occurs more frequently in athletes even though athletes receive more alcohol-related education than non-athletes. Athletes were more likely to identify "interference with performance" as a reason to abstain from drinking. Implications Alcohol abuse is a huge problem among college athletes. Additionally, while this study chose to focus on a collegiate population, many of the traits that lead to alcohol abuse are present in high school aged children as well. Several important implications arise from this study that should apply to high school and collegiate program alike: Recognize that alcohol abuse is a problem with athletes, including swimmers, and don't be afraid to address the issue. In educational efforts, emphasize the detrimental effect alcohol can have on athletic performance, since this reason is cited most often for abstaining from alcohol. Work to change the social environment your athletes live in to reduce peer pressure. Encourage the team to develop a goal of abstaining from alcohol.